2019
DOI: 10.1002/pon.5228
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life by human immunodeficiency virus status in a cross‐sectional survey of gay and bisexual prostate cancer survivors

Abstract: Objective Prostate cancer is the most common invasive cancer in gay and bisexual men (GBM). Despite the unique sexual and urinary concerns of this group, studies of prostate cancer rehabilitation have primarily focused on heterosexual men. GBM also have high prevalence of human immunodeficiency virus (HIV), which may be associated with lower health‐related quality of life (HRQOL). We examined the association between HIV status and HRQOL in a cohort of GBM with prostate cancer. Methods Data from the Restore stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Overall, MSM reported more genitourinary challenges than heterosexual peers, including worse urinary and bowel function, lack of ejaculation, changes to erectile function, climacturia, pain during anal sex, penile shortening, loss of libido, and less frequency of sexual activity, although one study demonstrated better sexual function in MSM diagnosed with prostate cancer than that reported in the literature [ 34 37 ]. MSM with HIV reported more significant detrimental effects of treatment than MSM without HIV [ 38 ]. One study showed that MSM had greater sexual dysfunction after bicalutamide monotherapy compared to heterosexual peers [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, MSM reported more genitourinary challenges than heterosexual peers, including worse urinary and bowel function, lack of ejaculation, changes to erectile function, climacturia, pain during anal sex, penile shortening, loss of libido, and less frequency of sexual activity, although one study demonstrated better sexual function in MSM diagnosed with prostate cancer than that reported in the literature [ 34 37 ]. MSM with HIV reported more significant detrimental effects of treatment than MSM without HIV [ 38 ]. One study showed that MSM had greater sexual dysfunction after bicalutamide monotherapy compared to heterosexual peers [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four subgroups of SGM appear most at risk of poorer outcomes. First, HIV-positive patients score worse on EPIC sexual and urinary subscales compared to HIV-negative patients, post-treatment (28). Second, when we compared Restore-1 participants by age, similar to heterosexual patients, the older cohorts scored worse on SF-12 scores for mental health and physical health (P<0.05).…”
Section: Which Groups Of Sgm Are At Greater Risk Of Poorer Outcomes From Prostate Cancer Treatment?mentioning
confidence: 93%
“…First, we conducted in-depth qualitative telephone interviews with 30 prostate cancer patients and nine partners or caregivers (23)(24)(25). Then, we conducted an online quantitative survey with 192 gay and bisexual and one transgender prostate cancer patients/ survivors living in North America (26)(27)(28)(29)(30)(31)(32). Participants were recruited from the largest online cancer support network providing groups for SGM prostate cancer patients.…”
Section: Summary Of Methodsmentioning
confidence: 99%
“…MSM reported more genitourinary challenges than heterosexual peers, including worse urinary and bowel function, lack of ejaculation, changes to erectile function, climacturia, pain during anal sex, penile shortening, loss of libido, and less frequency of sexual activity [37,50,51]. MSM with HIV reported more signi cant detrimental effects of treatment than MSM without HIV [44]. One study showed that MSM had greater sexual dysfunction after bicalutamide monotherapy compared to heterosexual peers [43].…”
Section: Prostate Cancer Survivorshipmentioning
confidence: 99%